Stability-indicating HPLC method for determination of amiodarone hydrochloride and its impurities in tablets: a detailed forced degradation study - Ana Silva Coelho; Igor Felipe Rodrigues Ribeiro; Eduardo Burgarelli Lages (Universidade de São Paulo, 2020)
Resumo Amiodarone hydrochloride is one of the most important drugs used to treat arrhythmias. The USP monograph for amiodarone hydrochloride describes an HPLC method for the quantification of seven impurities, however, this method shows problems that result in unresolved peaks. Moreover, there is no monograph for tablets in this compendium. Thus, a stability indicating HPLC method was developed for the determination of amiodarone, its known impurities and degradation products in tablets. A detailed forced degradation study was performed submitting amiodarone API, tablets and placebo to different stress conditions: acid and alkaline hydrolysis, oxidation, metal ions, heat, humidity, and light. Amiodarone hydrochloride API was susceptible to degradation in all stress conditions. The tablets also showed degradation in all environments, except in acidic condition. The analytes separation and quantification were achieved on an Agilent Zorbax Eclipse XDB-C18 column (100 x 3.0 mm, 3.5 µm). The mobile phase was composed of 50 mM acetate buffer pH 5.5 (A) and a mixture of methanol-acetonitrile (3:4, v/v) (B) in gradient elution. The method was validated in the range of 350-650 µg/mL for assay and 10-24 µg/mL for impurities determination. Therefore, this method can be used both for stability studies and routine quality control analyses.